2017
DOI: 10.1111/jon.12483
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of Brain MRI Segmentation Algorithms: Empirical Comparison of Local MAP PSTAPLE, FreeSurfer, and FSL‐FIRST

Abstract: BACKGROUND AND PURPOSE Segmentation of human brain structures is crucial for the volumetric quantification of brain disease. Advances in algorithmic approaches have led to automated techniques that save time compared to interactive methods. Recently, the utility and accuracy of template library fusion algorithms, such as Local MAP PSTAPLE (PSTAPLE), have been demonstrated but there is little guidance regarding its reproducibility compared to single template‐based algorithms such as FreeSurfer and FSL‐FIRST. ME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
59
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 59 publications
(114 reference statements)
8
59
0
Order By: Relevance
“…In particular, the MD‐GRU segmentation approach showed improved reproducibility in the anatomically most challenging region of the BS—the medulla oblongata. Despite relatively high reproducibility compared to other available techniques in earlier studies (Velasco‐Annis et al, ), FreeSurfer segmentations can present inconsistencies especially in the caudal part of the MO. In this part, as well as in the region at or below the level of the central canal entry into the medulla, the differences between medulla and CSF tissue characteristics may lead to anatomically incorrect segmentations.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In particular, the MD‐GRU segmentation approach showed improved reproducibility in the anatomically most challenging region of the BS—the medulla oblongata. Despite relatively high reproducibility compared to other available techniques in earlier studies (Velasco‐Annis et al, ), FreeSurfer segmentations can present inconsistencies especially in the caudal part of the MO. In this part, as well as in the region at or below the level of the central canal entry into the medulla, the differences between medulla and CSF tissue characteristics may lead to anatomically incorrect segmentations.…”
Section: Discussionmentioning
confidence: 89%
“…A recent study by Velasco‐Annis et al () compared three originally for brain segmentation designed, automated BS segmentation methods (FSL‐FIRST (Patenaude et al, ), PSTAPLE (Akhondi‐Asl & Warfield, ), FreeSurfer (Fischl et al, ; Fischl et al, ; Iglesias et al, ) and reported highest reproducibility of BS segmentations performed by FreeSurfer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…segmentation and automatic brain segmentation (ABS) [2]. Both manual and semiautomatic segmentations require manual delineation of brain regions, which are unavoidably susceptible to intra-and inter-rater inconsistency [2,3]. In contrast, ABS is hand-free and thus more resistant to inter-rater variability.…”
mentioning
confidence: 99%
“…The atlas that contains brain anatomy information is used as a reference for the segmentation of new MRI images [3]. Labels of brain regions from the atlas are modulated by affine transformations to fit target images [2]. FreeSurfer encompasses template registration and segmentation, and it can measure not only the volumes of many anatomical structures [13] but also other brain structural features such as cortical thickness, surface area, intensity and curvature.…”
mentioning
confidence: 99%